2022
DOI: 10.1155/2022/9050686
|View full text |Cite
|
Sign up to set email alerts
|

Dracorhodin Perchlorate Regulates the Expression of Inflammatory Cytokines through the TLR4 Pathway and Improves Skin Wound Healing in Diabetic Rats

Abstract: Background. Dragon’s blood is a natural medicine with hemostatic and blood-activating effects and is used to promote wound healing. Dracorhodin perchlorate (DP) is a stable form of dracarhod and is used as a substitute for cochinchinenin. DP promotes the proliferation of rat fibroblasts and promotes wound healing in rats. Methods. DP ointment (0.2 mg/mL) was applied to the skin wounds of nondiabetic and diabetic rats, and the skin of the wound was collected. Wound healing rate, H&E staining, Masson stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It was noted that comparing with the model group, the expressions of both EGF and bFGF were significantly increased after 21 days in both inflammation targeting and non-targeting emulsion gel groups ( p < 0.05), whereas the expression of EGF was significantly increased after 14 days in inflammation, targeting the emulsion gel group (* p < 0.05). All these findings indicated that dracorhodin perchlorate could promote the expression of both EGF and bFGF in the wound tissues [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Moreover, inflammation-targeted emulsion gel was observed to be more suitable for use because of its potent inflammation targeting properties.…”
Section: Resultsmentioning
confidence: 99%
“…It was noted that comparing with the model group, the expressions of both EGF and bFGF were significantly increased after 21 days in both inflammation targeting and non-targeting emulsion gel groups ( p < 0.05), whereas the expression of EGF was significantly increased after 14 days in inflammation, targeting the emulsion gel group (* p < 0.05). All these findings indicated that dracorhodin perchlorate could promote the expression of both EGF and bFGF in the wound tissues [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Moreover, inflammation-targeted emulsion gel was observed to be more suitable for use because of its potent inflammation targeting properties.…”
Section: Resultsmentioning
confidence: 99%
“…Among these components, dracorhodin and rhein were characteristic. Dracorhodin could promote the proliferation of fibroblasts [ 32 ] and keratinocytes [ 33 ] during wound healing. In addition, dracorhodin can inhibit the secretion of IL-1α and TNF-α, alleviate inflammation, stimulate the expression of vascular endothelial growth factors and TGF, and promote fibroblast proliferation and collagen deposition [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed that DP can promote fibroblast proliferation, collagen formation, and inhibit scar growth; accordingly, it is widely used in scarless wound healing (Jiang et al, 2018;Jiang et al, 2017;Lu et al, 2021;Xiong et al, 2022). Moreover, it is often used as adjuvant treatment for refractory wounds (Lingli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%